Prevalence of Human Immunodeficiency Virus (HIV) and chronic Hepatitis C Virus (HCV) coinfection in people treated at a Referral Service in Southern Brazil (Research, Society and Development, 2022)
This study aimed to evaluate the prevalence of HIV/HCV coinfection and associated factors in people living with HIV/AIDS enrolled in a Specialized Care Service in Southern Brazil (Pelotas, RS). For methodology, a descriptive retrospective outpatient study was carried out with 1,017 people living with HIV/AIDS, aged 18 years or older, enrolled in the SAE between 2009 and 2014. The analyzed characteristics were divided into three levels: sociodemographic (gender, skin color, age, schooling in years of study), behavioral (home arrangement, smoking status, alcohol use, illicit drug use and injectable drug use, blood transfusion, heterosexual and homosexual contact) and clinical (diabetes, dyslipidemia, hepatic steatosis, hepatitis B, obesity, first CD4 count and lowest CD4 count). The results showed a prevalence of HIV/HCV coinfection in the assessed individuals in 8.3% (84/1,017). Women living with HIV had a 35% lower prevalence of HIV/HCV coinfection than men living with HIV. Injectable drug use (32.4%) had more than twice the HIV/HCV coinfection rate. Moreover, patients with hepatitis B (25%) had a sixfold higher prevalence rate of HIV/HCV coinfection. We concluded that male individuals, injectable drug use, and patients with hepatitis B are more likely to have HIV/HCV coinfection. It is important to implement comprehensive strategies for preventing, diagnosing, and treating viral hepatitis in people living with HIV/AIDS.